Diagnostic accuracy of language sample measures with Persian-speaking preschool children. (April 2015) - Kazemi, Yalda; Klee, Thomas; Stringer, Helen
Abstract: This study examined the diagnostic accuracy of selected language sample measures (LSMs) with Persian-speaking children. A pre-accuracy study followed by phase I and II studies are reported. Twenty-four Persian-speaking children, aged 42 to 54 months, with primary language impairment (PLI) were compared to 27 age-matched children without PLI on a set of measures derived from play-based, conversational language samples. Results showed that correlations between age and LSMs were not statistically significant in either group of children. However, a majority of LSMs differentiated children with and without PLI at the group level (phase I), while three of the measures exhibited good diagnostic accuracy at the level of the individual (phase II). We conclude that general LSMs are promising for distinguishing between children with and without PLI. Persian-specific measures are mainly helpful in identifying children without language impairment while their ability to identify children with PLI is poor.